Solar-blind ultraviolet detectors based on high-quality HVPE α-Ga2O3 films with giant responsivity - Almaev, Aleksei V.; Nikolaev, Vladimir I.; Kopyev, Viktor V.; Shapenkov, Sevastian; Yakovlev, Nikita N.; Kushnarev, Bogdan O.; Pechnikov, Aleksei I.; Deng, Jinxiang; Izaak, Tatyana I.; Chikiryaka, Andrei V.; Scheglov, Mikhail P.; Zarichny, Anton (IEEE sensors journal)
The MSM structures based on high-quality 1.6- μm -thick α -gallium oxide (Ga2O3) films grown by the halide vapor phase epitaxy with Ti/Ni interdigital contacts were developed for the detection of short-wave ultraviolet (UVC) radiation. The spectral dependences of responsivity, external quantum efficiency (EQE), and detectivity of MSM structures based on α -Ga2O3 were studied in the wavelength range of 205–260 nm. The responsivity, the EQE, and the detectivity are 7.19×104 A ×W−1 , 3.79×105 arb.un., and 1.12×1018 Hz 0.5× cm ×W−1 , respectively, for structures with an interelectrode distance of 30 μm at an applied voltage of 10 V and exposure to radiation with a wavelength of 235 nm. The high values of the photoelectric characteristics were caused by the manifestation of an internal gain of the photoresponse due to the self-localization of holes in α -Ga2O3. The prospects of researches to develop UVC radiation detectors for wireless UVC communication were shown.